Assessing The Effect of Selected Cleaning Agents (Bleach, Ethanol and Liquid soap) On Selected Nosocomial Organisms (Escherichia. coli, Staphylococcus aureus, Pseudomonas aeruginosa) in Uganda. A Case Study of Kisubi Hospital. - Faith Nakachwa; David Serunjogi; Kizito Muwonge (Student's Journal of Health Research, 2021)
Background The major cause of disease and even human death are bacteria. Disinfectant is widely used in various ways as an effective agent to kill or eliminate bacteria, especially in the microbial laboratory. The most commonly used disinfectants in the laboratory are ethanol, bleach, and hand soap. This study assessed the effect of the common cleaning agents against bacteria. Methodology It was an experimental study on disinfectant efficacy of ethanol, bleach, and antibacterial handwashing soap on surface disinfection. Sampling was carried out between April and June of 2017. The samples were collected from our lady of Consolata kisubi hospital which is located on Nkima Road- Kisubi, Wakiso, Uganda. The samples collected were obtained from the hospital surfaces like door handles, beds, random floors, toilets, and work surfaces before and after cleaning. Results 64 samples were collected from 32 sites. The selected nosocomial organism in the study included E.coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Among the selected disinfectants, ethanol was the most effective against the available selected nosocomial organisms. Conclusion Bacteria is present on so many surfaces of the hospital, and the selection of appropriate cleaning agents is vital to achieving maximum cleaning. Bleach and liquid soap should not be used in combination if cleaning different surfaces in the hospital due to the effects of the inorganic compounds that might be present in the liquid soap that inactivates active ingredients used present in the Bleach. Recommendation The hospital should come up with a minimum inhibitory concentration of the disinfectants that is effective to be used. The support staff in charge of cleaning should be trained on the right way of cleaning and disinfecting.